Case report: Bi-atrial thrombus after occlusion of atrial septal defect with acute cerebral infarction and pulmonary embolism - Xiong, Wei; Tang, Li; Long, Wei; Liu, Jin; Song, Haibo (Frontiers in Cardiovascular Medicine, 2022)
A 49-year-old male presented to hospital with symptoms of acute cerebral infarction and pulmonary embolism who underwent transcatheter closure of atrial septal defect a year before. Transthoracic echocardiography showed a 13×9 mm hypoechoic mass attached to the left-atrial side of the device, which was suspected to be a neoplasm or thrombus. The patient was indicated for surgery after multidisciplinary discussion due to ineffective medical therapy and typical stroke and pulmonary embolism symptoms. Three-dimensional transesophageal echocardiography (3D-TEE) revealed left-atrial vegetation (21×16 mm) and right-atrial vegetation (8×6 mm) attached to the device, which were confirmed as thrombus by surgical separation and laboratory examination. This case highlights the importance of 3D-TEE and a multidisciplinary team in the diagnosis and therapy of device-related thrombus.